Micropatterned array to assess the interaction of single platelets with platelet factor 4-heparin-IgG complexes - Medvedev, Nikolay; Palankar, Raghavendra; Krauel, Krystin; Greinacher, Andreas; Delcea, Mihaela (Thrombosis and Haemostasis, 2014)
We report a strategy to generate by electron beam lithography high fidelity micropatterned arrays to assess the interaction of single platelets with immobilised ligands. As a proof-of-principle we functionalised the microarrays with platelet factor 4 (PF4)-heparin-IgG complexes. We embedded biotinylated water-soluble quantum dots into polyethylene glycol (PEG)-coated micropatterned arrays and functionalised them via streptavidin to bind biotinylated ligands, here biotinylated-PF4/heparin complexes. The integrity of the PF4/heparin-complexes was shown by binding of anti-PF4/heparin antibodies. Ligand density was quantified by immunofluorescence and immunogold antibody labelling. Real-time calcium imaging was employed for read-out of single platelets activated on micropatterned surfaces functionalised with PF4/heparin-IgG complexes. With the smallest micropatterns (0.5x0.5 µm) we show that single platelets become strongly activated by binding to surface-immobilised PF4/heparin-IgG, while on larger micropatterns (10x10 µm), platelet aggregates formed. These findings that HIT antibodies can cause platelet activation on microarrays illustrate how this novel method opens new avenues to study platelet function at single cell level. Generating functionalized microarray surfaces to which highly complex ligands can be bound and quantified has the potential for platelet and other cell function assays integrated into high-throughput microfluidic microdevices.
Keywords: Heparin-induced thrombocytopenia; platelet factor 4; micropatterned arrays; electron beam lithography; platelet activation